STRATEGI PENINGKATAN PENJUALAN PROPERTI PADA PT. AMANAH SULAWESI TENGGARA - Adriatin Adi, Vivin; Paula Tamburaka, Irmawati; Suriadi, La Ode (JPEP (Jurnal Progres Ekonomi Pembangunan), 2019)
This research aims to analyse the strategy for propertysales improvement at PT.Â  Amanah Sultra. Data used in this research is primary data collected from the employees of PT. Amanah Sultra. Amount of population in this research are 45 people and the sample research are 15 people of PT. Amanah Sultra employees. Data analysis applied is SWOT Analysis Method.Result of the research shows that there are four strategies that can be applied in improving the sales property profit at PT. Amanah Sultra. The four strategies are: a. SO Strategy: 1. Continuously innovating and improving the products quality in order to surpass competition with other same companies. 2. Improving and widening market networking in order to influence costumer in their decision making on choosing housing products. ST Strategy: 1. Continuously innovating and improving the products quality in order to surpass competition with other same companies. 2. Improving and widening market networking in order to influence costumer in their decision making on choosing housing products. C. WT Strategy: PT. Amanah Sultra conductsvission and mission generalization to the employees through training until the purpose of the company achieved in order to improve the customer trust towards the company. D. WT Strategy: PT. Amanah Sultra continuously improves the relationship quality of internal and external within the company in order to surpass competition with other same companies.Â